RELIABILITY ALLOCATION OF FUEL CELL VEHICLE BASED ON GREY SYSTEM THEORY - LI Tong; ZHENG SongLin; CHEN Tie; FENG JinZhi; ZHAO LiHui (Jixie qiangdu)
In order to solve the problem of the lack of reliability data and the uncertain factors in the product development stage,a reliability allocation model based on grey system theory was proposed. Considering 6 effecting factors such as the importance,complexity, technology development level, manufacturing level, working time and environmental conditions,combining with the expert experience and known reliability data,the relative failure relationship among fuel cell vehicle subsystems was elevated using improved method of solving index weight based on grey correlation. The reliability of each subsystem was allocated according to the comprehensive grey evaluation value. Compared with the actual failure data,the validity of this model was verified.